1996
DOI: 10.1113/jphysiol.1996.sp021230
|View full text |Cite
|
Sign up to set email alerts
|

Effects of immunization against an autocrine inhibitor of milk secretion in lactating goats.

Abstract: 1. Lactating goats were immunized against the goat's milk protein identified as a feedback inhibitor of lactation (FIL). Immunization was by three treatments during the declining stage of lactation. 2. When antibodies to FIL were consistently detected in milk (in response to the third treatment), the rate of decline in milk secretion was significantly reduced compared with sham-immunized controls. Such a response was not apparent with the first two treatments when serum but not milk titres of anti-FIL were rai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1996
1996
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 15 publications
1
9
0
Order By: Relevance
“…The fact that fat concentration did not vary significantly seems in agreement with the reports of Wilde et al (1988Wilde et al ( , 1996, who stated that the FIL is involved in the modulation of the synthesis of all the major components of milk, so that the composition of milk would not be affected by changes in milking frequency.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The fact that fat concentration did not vary significantly seems in agreement with the reports of Wilde et al (1988Wilde et al ( , 1996, who stated that the FIL is involved in the modulation of the synthesis of all the major components of milk, so that the composition of milk would not be affected by changes in milking frequency.…”
Section: Discussionsupporting
confidence: 90%
“…Instead, the concentration of protein was significantly higher in ODM than TDM udder halves in Sarda and Merino breeds. So it appears that the reports of Wilde et al (1988Wilde et al ( , 1996 that milk composition would be unaffected by changes in the milking frequency cannot be applied in the same manner to fat and protein.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The protein, which has been named FIL (feedback inhibitor of lactation), also inhibited milk secretion reversibly when added to milk in the goat's udder (Wilde et al 1995). Active immunization against FIL in lactating goats produced a temporary reversal of the decline in milk production that normally occurs in late lactation (Wilde et al 1996). FIL is synthesized in the same mammary epithelial cells that synthesize other milk constituents, and so feedback inhibition is an autocrine mechanism, that is, the luminal epithelial cells secrete an inhibitor of their own secretory activity.…”
Section: Milking Frequency and Efficiencymentioning
confidence: 99%
“…Next, we investigated the relationship between SCC and S. aureus counts and SCC and the proportion of cytokeratin-positive cells in the milk of mastitis models; however, the correlations in these relationships were not significant (Figs 3,4). Previous studies demonstrated that the SCC in milk is affected by many factors, such as cattle species, milk production level, and lactation stage, among others ( (Wilde et al 1996;Long et al 2001), little is known about the effect of intramammary-infected bacterial loads on MEC exfoliation into milk in mastitis caused by S. aureus. Next, we examined by flow cytometry analysis the proportion of cytokeratin-positive cells, specifically MEC, in SCC after S. aureus infusion.…”
Section: Discussionmentioning
confidence: 99%